(untitled) (Research, Society and Development, 2021)
The aim of this study was to characterize the breast meat from broilers affected by the white striping myopathy and examine its influence on meat quality. 180 breast samples from male broilers, slaughtered at 42-d-old, were used. Samples were classified according to the severity degree of apparent white stripes on the Pectoralis major muscle surface (“normal” [n=60], “moderate” [n=60], or “severe” [n=60]). Birds affected by the myopathy produced breast meat with higher L*, a* and b* values on the outer surface. Cooking loss decreased as the severity degree increased (30.94% [normal] to 21.65% [severe]). Toughness increased in the samples classified as moderately and severely affected. There was also an increase in the concentrations of lipids (1.60% [normal] to 2.57% [affected samples], on average), cholesterol (84.60 mg/100 g [normal] to 91.73 mg/100 g [severe degree]) and collagen as the severity degree increased. Although there are statistical differences for some evaluated parameters and, even so, these results are considered numerically normal based on previously published literature, we emphasize that the white striping abnormality alters chicken breast meat quality, especially regarding to the protein and fat concentrations, which can offer consumers products with nutritional quality different from the average specified on the packaging.